A Survey of Homomorphic Encryption for Nonspecialists. (11th December 2007) - Fontaine, Caroline; Galand, Fabien
Abstract : Processing encrypted signals requires special properties of the underlying encryption scheme. A possible choice is the use of homomorphic encryption. In this paper, we propose a selection of the most important available solutions, discussing their properties and limitations.